Impact of High-Dose Statin Therapy on Occurrence of In-stent Restenosis following Percutaneous Coronary Intervention: An Observational Study - Parvez, Muzdalfa; Khan, Farhat Ullah; Khan, Naeem; Khan, Qasim Ullah; Khan, Imran; Khan, Muhammad Idrees (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the impact of high-dose statin therapy on the occurrence of ISR following PCI and to assess whether high-dose statins reduce ISR and improve post-PCI outcomes. Methodology: A retrospective observational study was conducted at Hayatabad Medical Complex, Peshawar between June 2021 and June 2022. A total of 250 patients were included, with 125 patients receiving high-dose statins and 125 in the control group. Data on stent thrombosis, ISR, and DAPT adherence were collected, with statistical analysis conducted using the chi-square test. Results: The results showed that 65% of control patients experienced stent thrombosis compared to 42% in the high-dose statin group (p-value = 0.0032). Regarding DAPT adherence, 80% of control patients adhered well to the therapy, compared to 55% in the statin group. Despite the lower adherence in the statin group, the incidence of ISR was still significantly reduced. The chi-square test for stent thrombosis yielded a p-value of 0.0032, indicating a significant association between statin therapy and reduced ISR. Conclusion:High-dose statin therapy significantly reduces the occurrence of ISR post-PCI, highlighting its therapeutic benefits beyond lipid-lowering effects. Future research should focus on multi-center trials and optimal dosing strategies for long-term ISR prevention.